FREQUENCY OF CANNABIS USE AND MEDICAL CANNABIS USE AMONG PERSONS LIVING WITH HIV IN THE UNITED STATES: FINDINGS FROM A NATIONALLY REPRESENTATIVE SAMPLE - Pacek, Lauren R. (AIDS Educ Prev, 2018)
Little is known about cannabis use frequency, medical cannabis use, or correlates of use among persons living with HIV (PLWH) in United States nationally representative samples. Data came from 626 PLWH from the 2005–2015 National Survey on Drug Use and Health. Logistic regression identified characteristics associated with frequency of cannabis use. Chi-squares identified characteristics associated with medial cannabisuse. Non-daily and daily cannabis use was reported by 26.9% and 8.0%. Greater perceived risk of cannabis use was negatively associated with daily and non-daily use. Younger age, substance use, and binge drinking were positively associated with non-daily cannabis use. Smoking and depression were associated with non-daily and daily use. One-quarter reported medical cannabis use. Medical users were more likely to be White, married, and nondrinkers. Cannabis use was common among PLWH. Findings help to differentiate between cannabis users based on frequency of use and medical versus recreational use.